A Multi-view Stereo Benchmark with High-Resolution Images and Multi-camera Videos - Schöps, Thomas Maximilian; Schönberger, Johannes L.; Galliani, Silvano; Sattler, Torsten; Schindler, Konrad; Pollefeys, Marc; Geiger, Andreas (2017 Conference on Computer Vision and Pattern Recognition (CVPR), 2017)
Motivated by the limitations of existing multi-view stereo benchmarks, we present a novel dataset for this task. Towards this goal, we recorded a variety of indoor and outdoor scenes using a high-precision laser scanner and captured both high-resolution DSLR imagery as well as synchronized low-resolution stereo videos with varying fields-of-view. To align the images with the laser scans, we propose a robust technique which minimizes photometric errors conditioned on the geometry. In contrast to previous datasets, our benchmark provides novel challenges and covers a diverse set of viewpoints and scene types, ranging from natural scenes to man-made indoor and outdoor environments. Furthermore, we provide data at significantly higher temporal and spatial resolution. Our benchmark is the first to cover the important use case of hand-held mobile devices while also providing high-resolution DSLR camera images. We make our datasets and an online evaluation server available at http://www.eth3d.net.